Bioequivalence of Fixed Dose Combination of Atorvastatin 10 mg and Aspirin 150 mg Capsules: A Randomized, Open-Label, Single-Dose, Two-way Crossover Study in Healthy Human Subjects - Tippabhotla, S. K.; Betha, M. R.; Gadiko, C.; Battula, R; Nakkawar, M.; Cheerla, R.; Khan, S. M.; Yergude, S.; Thota, S.; Vobalaboina, V. (Drug Research, 2013)
The present study evaluated the bioavailability and bioequivalence of fixed dose combination test formulation (atorvastatin 10 mg and aspirin 150 mg capsule) against marketed reference formulations (Lipitor® tablets 10 mg and Nu-Seals tablets 75 mg). This study was an open label, balanced, randomized, 2-treatment, 2-period, 2-sequence, single dose, crossover trial in 80 healthy adult human volunteers under fasting conditions. Plasma concentrations of atorvastatin, aspirin and salicylic acid were quantified using LC-MS/MS method. Pharmacokinetic parameters were estimated by noncompartmental model and mean pharmacokinetic parameters were comparable between test and reference formulations. The mean pharmacokinetic parameters (AUC0-t, AUC0-∞, Cmax, Cmax /AUC0-t and Cmax/AUC0-∞) for atorvastatin test and reference formulations were (52.69 ng.h/mL, 55.64 ng.h/mL, 9.45 ng/mL, 0.18 1/h and 0.17 1/h) and (52.20 ng.h/mL, 55.38 ng.h/mL, 10.25 ng/mL, 0.20 1/h and 0.19 1/h) respectively; and for aspirin were (1 378.62 ng.h/mL, 1 383.90 ng.h/mL, 1 022.18 ng/mL, 0.75 1/h and 0.75 1/h) and (1 314.17 ng.h/mL, 1 314.50 ng.h/mL, 985.90 ng/mL, 0.75 1/h and 0.75 1/h) respectively. Where as for salicylic acid, above parameters were (42 357.57 ng.h/mL, 44 139.47 ng.h/mL, 9 820.15 ng/mL, 0.24 1/h and 0.23 1/h) and (40 217.08 ng.h/mL, 42 032.44 ng.h/mL, 9 569.18 ng/mL, 0.24 1/h and 0.24 1/h) respectively for test and reference formulations. The 90% confidence intervals of atorvastatin and salicylic acid for AUC0-t, AUC0-∞, Cmax, Cmax /AUC0-t and Cmax/AUC0-∞ parameters were found to be within the acceptable regulatory bioequivalence limits. In conclusion, the new fixed dose combination test formulation was bioequivalent to the reference formulations under fasting conditions.
Keywords: atorvastatin; aspirin; salicylic acid; bioequivalence; WinNonlin; LC-MS/MS; within subject variability